(untitled) (Research, Society and Development, 2021)
This experiment aimed to analyze the temperature behavior of photovoltaic modules, with the efficiency of the on-grid photovoltaic system, installed at the State University of West Paraná - UNIOESTE, campus of Cascavel, Paraná. The photovoltaic system consists of two ropes, with a total power of 3.3 kWp. In the first period, it was found that the panel kept clean (Panel 2), during data collection, reached a higher efficiency during the first weeks and practically the same for the last weeks, compared to the dirty panel. Achieve an average efficiency of 13.73% and 14.39%, Panel 1 and Panel 2, respectively. For the second period, the average efficiency of both panels, with inclinations of 21° and 26°, was very close, being 14.25% (Panel 1) and 14.24% (Panel 2). The third period showed a difference in the efficiency of the panels, 13.7% (Panel 1) and 14.54% (Panel 2), with inclinations of 21° and 18°, respectively. The test of means identified that there was a difference between the levels of soiling of the modules, as well as their inclinations of 21° and 18°. As for the 21° and 26° inclinations, there was no significant difference, according to the Tukey Test at 5% significance.